Effects of Project Based Learning on Student Achievement: Understanding of Science Concepts, Intermediate Process Skills, and Creativity - Zakiyyah*, Zakiyyah; Fatnah, Nurwanti; Amelia, Fera (Universitas Syiah Kuala, 2024)
The research explores the dynamic landscape of education in Indonesia, marked by ongoing changes and enhancements across multiple domains. These transformations encompass curriculum revisions, improvements in educational standards, upgrades in school infrastructure, and advancements in the professional capabilities of educators including teachers and educational administrators. A primary objective of these reforms is to equip students with the competencies requisite for success in the 21st century, notably critical thinking, collaboration, communication, and creativity, often referred to as the 4Cs.This research uses a mixed-methods model, combining qualitative and quantitative data. Initial research is conducted through observation and interviews, followed by pretest and posttest given to students. The results show a significant improvement in students' understanding of scientific concepts, scientific process skills, and creativity after implementing project-based learning (PjBL). Additionally, students' response to PjBL is positive.The research concludes that PjBL affects students' understanding of scientific concepts, scientific process skills, and creativity. However, internal and external factors such as students' interest, motivation, learning environment, teachers, and learning materials also influence the effectiveness of learning.This research employs a mixed-methods approach, integrating both qualitative and quantitative data. Initial investigation involves observations and interviews, followed by administering pretests and posttests to students. The findings demonstrate a notable enhancement in students' comprehension of scientific concepts, scientific process skills, and creativity subsequent to the implementation of PjBL. Moreover, students' reception of PjBL is affirmative.